To solve the equation \( 3(x - 5) + 2x = 0 \), we can break it down step by step and fill in the blanks as we go.
-
Distribute the \(3\):
\(3(x - 5) = 3x - 15\)
Therefore, the equation becomes: \[ 3x - 15 + 2x = 0 \] -
Combine like terms:
Combine \(3x\) and \(2x\): \[ (3x + 2x) - 15 = 0 \rightarrow 5x - 15 = 0 \] -
Add \(15\) to both sides:
\[ 5x - 15 + 15 = 0 + 15 \rightarrow 5x = 15 \] -
Divide both sides by \(5\):
\[ \frac{5x}{5} = \frac{15}{5} \rightarrow x = 3 \]
So, filling in the blanks, the steps can be summarized as follows:
- Distribute: \(3(x - 5) \rightarrow 3x - 15\)
- Combine like terms: \(3x - 15 + 2x \rightarrow 5x - 15\)
- Add \(15\): \(5x - 15 = 0 \rightarrow 5x = 15\)
- Divide by \(5\): \(x = 3\)
Final answer: \(x = 3\).